Ion-Pair Formation in Neutral Potassium-Neutral Pyrimidine Collisions: Electron Transfer Experiments - Mendes, Mónica; Pamplona, Beatriz; Kumar, Sarvesh; da Silva, Filipe Ferreira; Aguilar, Antonio; García, Gustavo; Bacchus-Montabonel, Marie-Christine; Limao-Vieira, Paulo (Frontiers in Chemistry, 2019)
We report novel data on ion-pair formation in hyperthermal (30–800 eV) neutral potassium collisions with neutral pyrimidine (Pyr, C4H4N2) molecules. In this collision regime, negative ions formed by electron transfer from the alkali atom to the target molecule were time-of-flight mass analysed and the fragmentation patterns and branching ratios have been obtained. The most abundant product anions have been assigned to CN– and C2H– and the electron transfer mechanisms are comprehensively discussed. Particular importance is also given to the efficient loss of integrity of the pyrimidine ring in the presence of an extra electron, which is in contrast to dissociative electron attachment experiments yielding the dehydrogenated parent anion. Theoretical calculations were performed for pyrimidine in the presence of a potassium atom and provided a strong basis for the assignment of the lowest unoccupied molecular orbitals accessed in the collision process. In order to further our knowledge about the collision dynamics, potassium cation (K+) energy loss spectrum has been obtained and within this context, we also discuss the role of the accessible electronic states. A vertical electron affinity of (–5.69±0.20) eV was obtained and may be assigned to a π_3^*(b1) state that leads to CN– formation.